Precursive Prolongation in the Préludes of Chopin - Sobaskie, James William (Journal of the Society for Musicology in Ireland, 2007)
The poetic allusiveness of Chopin’s Préludes, Op. 28 (1839), intrigues and inspires - yet remains remarkably elusive. However, the concept of ’precursive prolongation’, founded on the Schenkerian notions of prolongation, diminution and structural levels, offers insight. Precursive prolongations, which include anticipations, appoggiaturas, secondary dominants and initial ascents, as well as elaborated versions of these plus those structures Heinrich Schenker called ’auxiliary cadences’, all are distinguished by the trait of prospective dependency. Expectations elicited by these tonal structures correspond to many of the allusive qualities we perceive in Chopin’s Préludes. This article begins with a survey of familiar precursive prolongations. It then proceeds to a definition that also distinguishes the concept of precursive prolongation from Schenker’s notion of auxiliary cadence. Next, analyses of several of Chopin’s Préludes (including those in C major, A major, B major, A-flat major, F minor and E minor) serve to demonstrate its ability to illuminate the structure and poetry of these pieces. The article concludes, among other findings, that many of Chopin’s Préludes exhibit a structural plan, described here as the ’attempt, attempt?achievement’ paradigm, that simulates a struggle to achieve a goal or to solve a problem by exploiting the suggestive power of precursive prolongation. Finally, the preludes in F minor and E minor are revealed to be most unusual tonal compositions in that each delays the first structural statement of its tonic harmony until its final bar, and each lacks a true fundamental line. Musical excerpts (accompanied by aural examples) and analytical sketches provide illustration.